Implementation of Guided Discovery Based Thematic Learning Modules to Improve Independence and Learning Achievement - Restika, Vika Nandhya; Wibowo, Mungin Eddy; Linuwih, Suharto (Journal of Primary Education)
This study aims to analyze the effect of integrative thematic modules based on the guided discovery in increasing independence and learning achievement. This study applied research and development (R & D) method which refers to the ten steps developed by Borg, and Gall. The test subjects were the fourth-grade students at SD N 1 Teluk and SD N 4 Teluk. The data collection was done using interviews, observation, questionnaires, and tests. The data analysis technique used in this study was descriptive analysis, ANOVA, and t-test. The results of the study showed that: guided discovery integrated thematic learning module that is produced effectively to improve independence and student independence and learning achievement. The students’ independence and learning achievement increases significantly based on paired t-test at a 0.05 level of significance (sig. (2 tailed) = 0.000 < a = 0.05).